499 Effects of Conventional Verse Organic Mineral Supplementation on Kid Birth Weight in Nubian Goats. (10th April 2018) - Rocco, C J; Stiegal, A M; Williams, T L; Williams, Z T
Abstract: Organic farming has recently grown in popularity and many conventional farms are following the trend, utilizing organic products such as organic concentrates or mineral supplements over conventional. Many organic producers claim superiority outcomes (i.e. increased weight gains, healthier animals, better yield) compared to conventional feedstuff. Although the push toward organic farming is strong, previous research is lacking in regards to nutritional benefits of organic diets. The objective of the study was to examine the effects of conventional verse organic mineral supplementation on birth weight at kidding. Ten pregnant Nubian does (n=5) ranging from 1 to 3 and BW varying 45 to 65 kg were separated and utilized in a completely randomized design study. Goats were fed one of two mineral supplements: an organic or conventional in the last 6 wks of gestation. Does were fed 28.3 g / d / 45.4 kg of body weight, of assigned mineral supplement and a 50:50 ration of corn and oats fed at 0.272 kg per 45.4 kg / d in individual feeders at 0700 and 1700 h. Both products were comparable in mineral content and observed by examining the effects on kid birth weight. Products closely accounted for amounts of calcium and phosphorus, a 2:1 ratio in the supplement, as recommended for dam and kid nutrition. Once parturition occurred kids were weighed and the does with kids were isolated into a goat maternity ward to be monitored. Differences in goat kid weight due to organic and non-organic treatments were analyzed by independent TTest at P<.05 using IBM S.P.S.S 22. No differences between kid birth weights were observed when does were fed organic verse conventional mineral supplementation (P=0.392). Similarly, research regarding organic products fed to goats found no differences in birth weight, growth rate and other factors between non-organic and organic groups. Differing results in data comparing organic and conventional treatments were mostly attributed to different feeding practices, less productive breeds or low forage resources. In conclusion, the organic mineral supplement was not more beneficial when compared to the conventional product. Thus, the increased price for the organic mineral supplement may not be justified for most producers.